Pengaruh Literasi Keuangan Terhadap Kinerja Keuangan Usaha Mikro Kecil dan Menengah (UMKM) dengan Perilaku Pengelolaan Keuangan sebagai Variabel Intervening: Studi Kasus pada UMKM di Kecamatan Alok Timur - Florentina Bene; Konstantinus Pati Sanga; Fransiscus De Romario (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This study aimed to determine the influence of financial literacy on the financial performance of MSMEs with financial management behavior as an intervening variable. The method used in this research was quantitative. The population in this study consisted of MSME actors in the East Alok District, totaling 1,548 MSME actors. The sampling technique employed simple random sampling with a total sample of 94 respondents. The type of data used in this study was primary data. The data collection procedure utilized questionnaires measured with a Likert scale. The data analysis technique used in this study was a simple linear analysis method, including descriptive statistical tests, data quality tests, classical assumption tests, hypothesis tests, and path analysis. The results of the study indicated that: (1) Financial literacy did not affect the financial performance of MSMEs, (2) Financial literacy affected the financial management behavior of MSMEs, (3) Financial management behavior did not affect the financial performance of MSMEs, and (4) Financial management behavior could not mediate the influence of financial literacy on the financial performance of MSMEs.